LAW ENFORCEMENT EFFORTS IN OVERCOMING CORRUPTION CRIMES COMMITTED BYINDONESIAN NATIONAL ARMY (TNI) - Wily Novan Prakoso; Firman Halawa; Rahmayanti (PT. Radja Intercontinental Publishing, 2024)
Corruption crimes committed by the TNI are criminal acts that must be resolved legally, because the TNI is a defense in the field of state security and must provide positive values. This article aims to find out the criminal responsibility of military members who commit criminal acts of corruption and the role of legal efforts in overcoming criminal acts of corruption committed by the Indonesian National Army in preventing criminal acts of corruption. The research method used is the normative juridical method with a descriptive analysis approach. The results of this research are that the TNI's authority is regulated in Law no. 31 of 1997 concerning Military Justice and Law no. 25 of 2014 concerning Military Discipline Law as stated in its duties and responsibilities in maintaining security and order in the unitary state of the Republic of Indonesia, enforcing the law, providing protection, protection and service to the community even when handling extraordinary criminal cases. Meanwhile, in carrying out investigations, the TNI and the Corruption Eradication Committee (KPK) also carry out investigations into complaints and further systematic handling is carried out by looking at procedural operational standards such as Law no. 31 of 1999 concerning Corruption Crimes.